Pentecostal Theological and Higher Education: From Tensions to Opportunities - Cartledge, Mark J. (Pneuma, 2024)
This essay offers an overview of the field of pentecostal and charismatic theological and higher education, engaging with the contributions of three recent books (Kay and Butler, 2023), Topf (2021), and Yong and Coulter (2023). It identifies several key tensions that emerged in the movement as it developed its institutional structures. It also pays attention to two contexts, namely (1) the Bible college and seminary context, and (2) the liberal arts and university context. Subsequently, Christian scholarship in its intellectual and cultural context is considered as a factor in the pentecostal and charismatic educational endeavor. Following this discussion, the essay explores future opportunities and issues that might be considered going forward. It provides an introductory piece for the articles that follow in this special issue and opens up the conversation before concluding by framing the educational mission of the church within its doxological life.